Complications and residual pleural thickening after intrapleural instillation of streptokinase with pigtail catheter drainage of tuberculous pleural effusion - S., Sandeepa H.; U., Narendra; Gaude, Gajanan S.; Sandeepa, Supriya (International Journal of Advances in Medicine, 2019)
Background: Tuberculosis is the most common cause of exudative lymphocytic pleural effusion in India. Residual pleural thickening (RPT) is observed in about 50 percent of patients even after proper treatment with ATT. Pleural fluid drainage either with simple aspiration or with intercostal drainage and addition of corticosteroids along with antitubercular drugs have not shown to influence the incidence of RPT. The present study was under taken to study the complications and residual effects of tubercular pleural effusion on the patients during the follow up period following intrapleural streptokinase instillation. Methods: Clinical profile, hospital course and outcome of tuberculous pleural effusion patients at the end of six months of anti-tubercular treatment of 50 patients from January 2009 to June 2010 were analyzed. These patients were randomly divided into two groups. One group (n=25) received intrapleural streptokinase via pigtail catheter and the other group (n=25) received intercostal drainage without intrapleural streptokinase instillation. All the patients received standard daily anti TB regimen of 2HERZ/4HR for a total duration of six months. All the patients were followed up for a total duration of 1 year for evidence of any residual pleural thickening. Results: Majority of the patients were above 40 years of age (60%). The male to female ratio was 2.3:1. The major symptoms of the patients were, fever in 44 patients (88%), cough in 42 patients (84%), breathlessness in 33 patients (66%), loss of appetite in 25 patients (50%) and chest pain in 25 patients (50%). Most of the patients had ADA levels between 40-70IU/L (48%) and only 6% had ADA levels below 40IU/L. The incidence of residual pleural thickening in the study group was less as compared to the control group (2.36±0.49mm vs 9.28±1.50mm) (p <0.0001). Conclusion: Intrapleural streptokinase instillation with pigtail catheter drainage less number of complications associated with study group and is successful with the decreased incidence of residual pleural thickening during the follow up period.